TiO2–CdS supported CuNi nanoparticles as a highly efficient catalyst for hydrolysis of ammonia borane under visible-light irradiation. (7th February 2020) - Sun, Dongdong; Hao, Yixin; Wang, Chenyang; Zhang, Xinghua; Yu, Xiaofei; Yang, Xiaojing; Li, Lanlan; Lu, Zunming; Shang, Wei
Abstract: TiO2 –CdS nanotubes (NTs) were used for the first time as a support to load metal nanoparticles (NPs) for the hydrolysis of ammonia borane (AB) which is a new strategy. The TiO2 –CdS NTs support was first synthesized using a hydrothermal method, and then the CuNi NPs were loaded using a liquid-phase reduction method. The synthesized samples were characterized by XRD, SEM-EDS, TEM, XPS, ICP, UV–Vis, and PL analyses. The characterization results show that the CuNi NPs existed in the form of an alloy with a size of ~1.2 nm and uniformly dispersed on the support. Compared with their single metal counterparts, the bimetallic CuNi-supported catalysts showed a higher catalytic activity in the hydrolysis of AB under visible-light irradiation: Cu0·45 Ni0·55 /TiO2 –CdS catalyst had the fastest hydrogen evolution rate with a high conversion frequency (TOF) of 25.9 molH2 ·molcat −1  min −1  at 25 °C and low activation energy of 32.8 kJ mol −1 . Cu0.45 Ni0.55 /TiO2 –CdS catalyst showed good recycle performance, maintaining 99.3% and 85.6% of the original hydrogen evolution rate even after five and ten recycles, respectively. Strong absorption of visible light, improved electron–hole separation efficiency, and metal synergy between Cu and Ni elements played a crucial role in improving the catalytic hydrolysis performance of AB. The catalyst prepared in this study provides a new strategy for the application of photocatalysts. Highlights: Inexpensive CuNi alloy nanoparticles supported on TiO2 –CdS nanotubes. CuNi/TiO2 –CdS facilitates the separation of photogenerated electrons and holes. CdS was first used to modify the band gap of TiO2 for hydrolysis of ammonia borane. Excellent ability to catalyze ammonia borane hydrolysis by visible light.